تحليل ممارسة إدارة الأرباح وفق نموذج ( Miller ) دراسة حالة مؤسسة EDOUGH خلال الفترة 2011 - 2021: Analysis of Earning Management according to the (Miller) model: EDOUGH case study During the Period 2011-2021 - بومنقار جيهاد,; بن علي سمية,; نصيب رجم, (Journal of North African Economies, 2025)
This study aims to identify Earnings Management and how to prospect it through the short-term benefits according to the “Mille Model” applied in EDOUGH institution for the period 2011-2021, Where the descriptive approach was used through previous studies to be the basic premise of the study, and the analytical approach was used through the analysis of financial data, as well as with regard to the process of prospecting for Earnings Management, The results showed that EDOUGH institution have exercised Earnings Management via short-term benefits for the duration of this study, but in varying proportions and in both directions up and down, furthermore this institution is familiar with Earnings Management practices, reaching 95% during our study. In other words, there is only 5% chance that the EDOUGH institution could abandon these practices